Paths to a Career in Copyright Leadership: When Metadata Met Copyright - Lewis, Mariah S. (Journal of Copyright in Education & Librarianship, 2022)
This article explores the experience of a librarian with a background in metadata and digital collections and the introduction of copyright into their career. It offers insight on how to handle copyright if it is added to your job description.